Micronutrient-Induced Activation of Nrf2 and -Elevation of Intracellular Antioxidants for Reducing Oxidative Stress and Chronic Infl ammation in Diabetes - Kedar N Prasad (Annals of Molecular and Genetic Medicine - Peertechz Publications, 2017)
Despite extensive research and dietary and lifestyle recommendations, the incidence of diabetes continues to increase. Diabetic medications have been useful in controlling blood levels of glucose; however, in general, the disease continues to progress rather slowly, and eventually leads to diabetic related complications. Analysis of published studies suggests that increased oxidative stress and  chronic inflammation initiate and promote the progression of diabetes and diabetic-related complications. Classical anti-diabetic measures are aimed at control of glucose levels and do not reduce these factors. Therefore, together with standard care and adoption of appropriate diet and lifestyle, attenuation of these biochemical defects may have utility in the prevention, and in combination with standard care, for the improved management of diabetes. The question arises how to maximally and at the same time reduce oxidative stress and inflammation. This review describes how simultaneous attenuation of excess oxidative stress and inflammation may be enabled. This briefly discusses diverse actions and cellular distributions of  different antioxidants in the body, and describes the effects of individual antioxidants in prevention and management of diabetes. It proposes that increasing the levels of antioxidant enzymes and dietary and endogenous antioxidant compounds at the same time is needed to decrease oxidative damage and chronic inflammation. An oral supplementation can increase the levels of antioxidant compounds; however, increasing the levels of antioxidant enzymes requires activation of Nrf2. This review discusses activation of Nrf2, and proposes a mixture of micronutrients that enhances the levels of antioxidant enzymes by activating the Nrf2 pathway, and also increases intracellular levels of antioxidant compounds. his combination is likely to have utility in patients with diabetes.